Land with low pH soil spread widely in Indonesia can be used for soybean (Glycine max) cultivation, although the production is low. The use of acid tolerant soybean and acid-Al tolerant nitrogen-fixing bacteria was an alternative way to increase soybean productivity on acid soils. This research was conducted to study the influence of acid-Al tolerant Bradyrhizobium japonicum on growth of Slamet cultivar soybean planted on acid soils in greenhouse. Three strains of acid-Al tolerant B. japonicum - ANGELIA REZTY FITRIANI SITUMORANG; NISA RACHMANIA MUBARIK; TRIADIATI TRIADIATI (Bogor Agricultural University, Indonesia, 2009)
Land with low pH soil spread widely in Indonesia can be used for soybean (Glycine max) cultivation, although the production is low. The use of acid tolerant soybean and acid-Al tolerant nitrogen-fixing bacteria was an alternative way to increase soybean productivity on acid soils. This research was conducted to study the influence of acid-Al tolerant Bradyrhizobium japonicum on growth of Slamet cultivar soybean planted on acid soils in greenhouse. Three strains of acid-Al tolerant B. japonicum, i.e. BJ 11 (19), BJ 11 (5), and BJ 11 (wt), were used in this experiment. The result showed that inoculation of all acid-Al tolerant B. japonicum strains could increase plant height, shoot and root weight, number of flowers, pods, seeds, seeds dry weight, and shoot and seed nitrogen content. Key words: Bradyhizobium japonicum, acid-aluminium tolerant, soybean, Slamet cultivar